AUTOMATION OF THE DRYING PROCESSES AND SELECTION OF THE ECUADORIAN COCOA CONSERVING SENSORY CHARACTERISTICS AND PREVENTING LABOR RISKS - Núñez Solano, Sergio Júlio (2017)
Cocoa in grain is a tropical fruit considered as a heritage in Ecuador and constitutes 60% of the premium quality in chocolates worldwide, has sensory characteristics unmatched by other producing countries. Manual drying and selection activities contain many occupational hazards, affecting the safety and well-being of the people involved in these tasks, with the ergonomic risk of an intolerable level requiring immediate intervention. This research provides safe automated mechanisms for operations through internationally validated methodologies, without affecting the sensory characteristics.